Cutaneous pleomorphic fibromas arising in patients with germline TP53 mutations. (6th April 2020) - Cloutier, Jeffrey M.; Shalin, Sara C.; Lindberg, Matthew; Gardner, Jerad M.; Fernandez‐Pol, Sebastian; Zaba, Lisa; Novoa, Roberto; Brown, Ryanne A.
Abstract: Pleomorphic fibromas are rare benign cutaneous neoplasms associated with deletion/loss of chromosomes 13q and 17p, where RB1 and TP53 are located, respectively. Herein, we report five cases of pleomorphic fibroma arising in patients with germline TP53 mutations, suggesting a potential link with Li‐Fraumeni syndrome. All three patients were female and young (mean age 27) with a strong personal and/or family oncologic history and confirmed pathogenic germline TP53 mutations. In two patients, multiple pleomorphic fibromas were diagnosed. Clinically, the lesions arose at various cutaneous sites and were small (≤2 cm) and raised (4/5). Histopathologically, the tumors were paucicellular, composed of atypical spindled to stellate cells with hyperchromatic and variably pleomorphic nuclei. Mitotic activity was exceedingly low, although rare atypical mitotic figures were seen in one case. Immunohistochemically, the tumor cells were diffusely positive for p16 (3/3) and showed loss of Rb expression (5/5). All cases showed aberrant p53 expression (overexpression in 4, complete loss in 1). The tumors have followed a benign clinical course with no evidence of progression or recurrence. In conclusion, the development of multiple pleomorphic fibromas in a young patient may be a clue to an underlying genetic cancer syndrome involving TP53 .